Faktor-Faktor Risiko Kenaikan Tekanan Darah pada Pekerja yang Terpajan Kebisingan di Bandara Ahmad Yani Semarang - Hastuti, Eny; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background : Ahmad Yani  Airport Semarang has a noise intensity level over the limit value of 85 dB(A). The Workers work continuously 8 hour a day. They may be exposed to aircraft noise over limit value that can make the blood pressure increases . The Objective of this research was to determine the factors related to the increasing of the blood pressure on workers in Ahmad Yani Airport. Method : This was an observational research using cross sectional design. Population was the workers of Ahmad Yani Airport, consist of  security unit, cargo unit and PKP-PK unit (Aircraft Rescue & Fire Fighting). Number of respondent was 60 workers. Data were analyzed using Chi-Square test and multivariate analysis using logistic regression. Result : This research found that (1) 33 peoples (55%) had systolic increased and 36 peoples (60%) had diastolic increased; (2) 45 peoples (75%) had noise exposed over 85 dB(A); (3) 22 peoples (36.7%) have been working over 10 years; (4) 18 peoples (30%) work over 8 hours/day; (5) 54 peoples (90%) are smoker; (6) 52 peoples (86.7%) did not wear ear protector equipment. Conclusions: (1). There are significant relationship between noise intensity, working duration, working hours and systolic blood pressure; (2). There are significant relationship between noise intensity,  working duration and diastolic blood pressure; (3). There are significant relationship between noise intensity and working duration  simultaneously and systolic blood pressure. Workers who has been working over 10 years and has noise exposere over 85 dB(A) has probability 68.7% for  systolic pressure increasing. Worker who has noise exposed over 85 dB(A) has probability 53.7% for diastolic pressure increasing. Key Words: Noise exposure, blood pressure, airport worker.